Hubungan Tingkat Pengetahuan Ibu Hamil Dengan Pelaksanaan Inisiasi Menyusui Dini Di Kute Desa Kaya Pangur - Hasanalita Hasanalita (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
National data on the coverage of babies who receive exclusive breastfeeding in 2020 is 66.06%. The achievement of exclusive breastfeeding in Aceh in 2019 was 55%, a decrease from the previous year of 61%. Factors that can influence exclusive breastfeeding include mother's characteristics (knowledge, education, occupation, age, parity and ethnicity), baby's characteristics (birth weight and baby's health condition), environment (beliefs, family support, place of residence and socio-economic ) and health services (pregnancy checks, lactation counseling, place of delivery, birth attendant and policies). Early Breastfeeding Initiation (IMD) is to provide an opportunity for newborns to breastfeed on their own within the first hour of their birth. IMD can prevent 22% of infant deaths in developing countries at the age of under 28 months, but if the first breastfeeding, when the baby is over two hours old and under the first 24 hours, it can prevent 16% of infant deaths under 28 days. The purpose of this study was to determine the relationship between the level of knowledge of pregnant women and the implementation of early breastfeeding initiation in Kute, Kaya Pangur Village. This research method is analytic with a cross sectional study design. The population of this study were all pregnant women who came to check their pregnancies in April 2022. The sample was taken by accidental sampling with a sample size of 35 pregnant women. The results showed that 29 pregnant women (82.9%) had a low level of knowledge, while 6 pregnant women (17.1%) had a high level of knowledge. 15 pregnant women (42.9%) had IMD during their previous delivery, while 20 pregnant women (57.1%) did not have IMD during their previous delivery. There is a significant relationship between the knowledge of pregnant women and the implementation of IMD (p value = 0.002). Knowledge of pregnant women influences the implementation of IMD in Kute, Kaya Pangur Village.